Pengaruh Semangat Kerja Terhadap Kinerja Pegawai Negeri Sipil pada Kantor Balai Standardisasi dan Pelayanan Jasa Industri di Samarinda (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of work spirit on employee performance of civil servants at the Standardization and Industrial Services Center (BSPJI) Samarinda. Work spirit is a crucial factor that influences employee productivity and performance outcomes. The research employs a quantitative approach using a sampling method. Data were collected through questionnaires distributed to 30 respondents who are employees of BSPJI Samarinda. The data were analyzed using simple linear regression to assess the impact of work spirit on performance. The results indicate that work spirit has a positive and significant effect on employee performance. This suggests that the higher the employees' work spirit, the better their performance. These findings highlight the importance for institutions to create a supportive work environment that maintains and enhances employee morale